2023
DOI: 10.1093/ndt/gfad105
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of renin–angiotensin–aldosterone system blockers in patients with Alport syndrome: a systematic review and meta-analysis

Abstract: Background Though renin-angiotensin-aldosterone system (RAAS) blockers have been considered the primary treatment for patients with Alport syndrome (AS) for a decade, there is no comprehensive review with evidence-based analysis evaluating the effectiveness of RAAS blockers in AS. Methods A systematic review and meta-analysis was performed of published studies that compared outcomes related to disease progression between pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Unfortunately, AS does not yet have a cure. Numerous research studies have substantiated the efficacy of angiotensin-converting enzyme inhibitors (ACEI) and angiotensin II receptor blockers (ARB) as therapeutic interventions for individuals with AS, effectively delaying the onset of failure of the kidneys in these individuals [26][27][28][29][30] . The proband in our study is treated with ACEI by oral administration, and her urine protein and red blood cells decreased compared with the previous treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, AS does not yet have a cure. Numerous research studies have substantiated the efficacy of angiotensin-converting enzyme inhibitors (ACEI) and angiotensin II receptor blockers (ARB) as therapeutic interventions for individuals with AS, effectively delaying the onset of failure of the kidneys in these individuals [26][27][28][29][30] . The proband in our study is treated with ACEI by oral administration, and her urine protein and red blood cells decreased compared with the previous treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no specific treatment for AS. ACEI and ARB are often used to treat AS and delay renal failure ( Yamamura et al, 2020b ; Zhang et al, 2021 ; Boeckhaus et al, 2022 ; Zeng et al, 2023 ). Recently, many studies have demonstrated the protective effect of SGLT-2 inhibitors in kidney disease ( Perkovic et al, 2019 ; Heerspink et al, 2020 ), and their therapeutic effects are still being investigated ( Mabillard and Sayer, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…"Genotype-phenotype" correlation and "genotype-response to therapy (Angiotensinconverting enzyme (ACE)-inhibition) correlation" have been described in hundreds of patients with Alport syndrome worldwide. 4 A previous investigator-initiated randomized Placebocontrolled trial in children two years and older, EARLY PRO-TECT Alport, 5 registry data, 6 trial concepts discussed with the FDA, 7 a case series, 8 as well as a recent meta-analysis,4 cumulated high quality good clinical practice (ICH-GCP) conform clinical data from children with Alport syndrome and chronic kidney disease, a unique tool to plan the first Pediatric randomized controlled trial in chronic kidney disease with SGLT2-inhibitors. The world's first pediatric randomized controlled trial, DOUBLE PRO-TECT Alport, is a proof of concept showing that -if a high unmet medical need meets academia -combined efforts of patient alliances and physicians can make things happen after a five-year planning phase: very positively, the idea for a Pediatric chronic kidney disease trial with SGLT2-inhibitors originates from industry.…”
Section: Main Textmentioning
confidence: 99%
“…In Alport syndrome, the international therapy recommendations recommend ACE-inhibitors, especially Ramipril, 19 as a specific therapy for oligo-symptomatic small children from the age of 2 years, because observational studies in Europe and Asia show a clear therapeutic effect and a randomized controlled trial also shows the safety in small children, as was recently the case summarized in a meta-analysis. 4 From a scientific point of view, the evidence for the off-label use of ACE-inhibitors such as ramipril in children with Alport syndrome in terms of delaying dialysis and improving life expectancy is far better than the evidence for the -approved -enzyme replacement therapy in Fabry disease. Nevertheless, ACE-inhibitors such as ramipril are not approved, quite the opposite of enzyme replacement therapy for Fabry disease.…”
Section: ) Legal Risk Aspects For Pediatricians Of Sglt2inhibitor Off...mentioning
confidence: 99%
See 1 more Smart Citation